Целый текст как объект стилистики текста - КОЖИНА, МАРГАРИТА Н. (Stylistyka, 2021)
Being а complex phenomenon text is studied Ьу а number of scientific branches of knowledge and in each of them - from its own viewpoint. However, even in terms of linguistics, in its diffe rent scientific trends this term is filled with diffe rent meaning i. е. considered as the highest level of language system, as а speech phenomenon (as а specific functioning of language, as а communication unit, etc.). Since there is а multitude of interpretations of the term 'text' it is significant to find coпelations among them and to make the definition more accurate. ln the present paper this term is considered in reference to stylistics of text in interdisciplinary context of studies (semantics of text, sociopsycholinguistics, linguocultual studies). Here is proved the expediency of distinction between terms-notions 'text' and 'integrated text (work)' which have both common and distinguishing characteristics. Being the object of functional stylistics, integrated text of any kind but not only of fiction and scientific text in particular has the numЬer of features characterizing this very text (but not the text as а level of language system). These features are: the existence of specific stylistic-speech organization, when the latter is caused Ьу author's conception, communication purposes, and on the whole - Ьу extralinguistics basis of work and given type of text; realization of conception of author who organizes all text elements (theme units, composition, architecture and others) into а single whole; the actual existence of such elements as composition, architecture, specific text units which acquire certain meaning only in the context of а definite integrated work (but not the meaning itselt); completeness of text as conception exhaustion on final moment of writing the work; conceptualism of work, etc.